If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 104 + 8x = 107 + 7x Solving 104 + 8x = 107 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 104 + 8x + -7x = 107 + 7x + -7x Combine like terms: 8x + -7x = 1x 104 + 1x = 107 + 7x + -7x Combine like terms: 7x + -7x = 0 104 + 1x = 107 + 0 104 + 1x = 107 Add '-104' to each side of the equation. 104 + -104 + 1x = 107 + -104 Combine like terms: 104 + -104 = 0 0 + 1x = 107 + -104 1x = 107 + -104 Combine like terms: 107 + -104 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 79+9x=94+4x | | 2(6+-7x+2x^2)=0 | | 10-.33333y=4+6x | | 9q^2+9q-10=0 | | 49=7j | | 4+5w-4w=4-2 | | z-7=36 | | 2-(1/4) | | (5x)+(x+20)+(2x)=180 | | 4+9(x)=184 | | (9*sqr-1)8(-6*sqr-4)= | | 20=x-4 | | w-50=16 | | -14=(6/7)x-4-7x | | (9*((-1)^1/2)*((-6)((-4)^1/2))= | | 6x-7=1+4x | | 47=p+14 | | 0.04(y-8)+0.02y=0.16y-0.9 | | -14=(6/7x)-4-7x | | 10x=3+12 | | (3w^2-7w+2)+(-4w^2+5w+1)= | | 5x-(7)=7x-(17) | | -3x-6=18forx | | 10x+4x+3+7=9x+3+4x | | 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 | | 9i*12i= | | 2(x+1)+5=-4(x-2) | | 5(3x+7)=-19+39 |